Identification of Cd3e{Open}, cd4 Cd8? Splice Variants of Atlantic Salmon - Imarai-Bahamonde, C; Maisey-Munoz, K; Toro-Ascuy, D; Reyes-Lopez, F; Montero, R (2011)
In vertebrates, CD3 complex and CD4 and CD8 co-receptors are essential for signal transduction during T cell activation. In the present study, we report the mRNA spliced variants of the Atlantic salmon CD3e{open}, CD4 and CD8? and the effect of pathogen encounter on the expression of these variants. CD3e{open} is alternatively spliced in thymus, head kidney, spleen and gills to give rise to the complete mRNA sequence and to an alternative product that lacks the transmembrane exon. CD4 is also alternatively spliced in the thymus, head kidney, spleen and gills to form two variants, although the alternative product is barely detectable. The alternative product lacks the exon 1B encoding the D1 domain, which is essential for binding to MHC class II proteins. Two amplicons were also found for the CD8? gene; sequencing analysis revealed that the main PCR product corresponds to the previously reported CD8? sequence, whereas the variant sequence encodes a potential protein that lacks the Ig-like domain. The expression of CD3, CD4, CD8? genes also analyzed in head kidney of LPS-treated and IPNV infected salmon and different patterns of expression were observed. The presence and balance of the different variants of T cell co-receptors could be related to the ability of fish to induce a particular type of immune response, as well as, the ability of the pathogen to modify the fish immune response. © 2011 Elsevier Ltd.